Diastereoselective Radical‐Type Cyclopropanation of Electron‐Deficient Alkenes Mediated by the Highly Active Cobalt(II) Tetramethyltetraaza[14]annulene Catalyst - Chirila, Andrei; Gopal Das, Braja; Paul, Nanda D.; de Bruin, Bas (ChemCatChem, 2017)
A new protocol for the catalytic synthesis of cyclopropanes using electron‐deficient alkenes is presented, which is catalysed by a series of affordable, easy to synthesise and highly active substituted cobalt(II) tetraaza[14]annulenes. These catalysts are compatible with the use of sodium tosylhydrazone salts as precursors to diazo compounds in one‐pot catalytic transformations to afford the desired cyclopropanes in almost quantitative yields. The reaction takes advantage of the metalloradical character of the Co complexes to activate the diazo compounds. The reaction is practical and fast, and proceeds from readily available starting materials. It does not require the slow addition of diazo reagents or tosylhydrazone salts or heating and tolerates many solvents, which include protic ones such as MeOH. The CoII complexes derived from the tetramethyltetraaza[14]annulene ligand are easier to prepare than cobalt(II) porphyrins and present a similar catalytic carbene radical reactivity but are more active. The reaction proceeds at 20 °C in a matter of minutes and even at −78 °C in a few hours. The catalytic system is robust and can operate with either the alkene or the diazo reagent as the limiting reagent, which inhibits the dimerisation of diazo compounds totally. The protocol has been applied to synthesise a variety of substituted cyclopropanes. High yields and selectivities were achieved for various substrates with an intrinsic preference for trans cyclopropanes. Cobalt on call: We present a new protocol for the synthesis of cyclopropanes using electron‐deficient alkenes catalyzed by a series of affordable, easy to synthesize, and highly active substituted cobalt(II) tetraazaannulenes.